Temperature and humidity regulating building material taking porous silicon-based mineral substance as base material and preparation method of temperature and humidity regulating building material

By using porous silicon-based minerals and combinations of potassium hydroxide, silicone, phase change microcapsules and other components, the problem of limited humidity regulation performance of existing humidity regulation building materials is solved, and the cost is low, simple process is simple, and temperature regulation is adjusted and humidity regulation is achieved. Both functions and effects.

CN119463546APending Publication Date: 2025-02-18LINHAI WEIXING NEW BUILDING MATERIALS CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411625409.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing humidity-regulating building materials have problems such as limited humidity regulation performance, complex process and high cost, and it is difficult to effectively adjust the relative humidity in the room, affecting human health and indoor environment quality.

Method used

Using porous silicon-based minerals as the substrate, combined with potassium hydroxide, silicone, phase-change microcapsules and other components, a low-cost and regulating combination is prepared through alkaline excitation and heat absorption and release mechanism of phase-change microcapsules. Temperature and humidity-regulating building materials with temperature and humidity-regulating functions.

Benefits of technology

It achieves better wet buffering performance, significantly improves humidity regulation effect, reduces cost, and is simple in process, suitable for commercial production and popularization of users.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463546A_ABST
    Figure CN119463546A_ABST
Patent Text Reader

Abstract

The invention relates to a temperature and humidity regulating building material taking porous silicon-based minerals as a base material and a preparation method of the temperature and humidity regulating building material. The temperature and humidity regulating building material comprises the following components in parts by weight: 3-22% of potassium hydroxide, 2-16% of silica gel, 0-7% of phase change microcapsules and the balance of silicon-based minerals. Compared with the prior art, the preparation method has the advantages that the internal microstructure of the material is adjusted from micron-sized particles to obtain a nano-structure through an alkaline excitation method, so that the total porosity of the coating and the number of open pores of less than 10nm are increased. The temperature and humidity adjusting coating is superior to the existing humidity adjusting coating sold in the market in humidity buffering performance, and has temperature adjusting and humidity adjusting functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a temperature and humidity regulating building material with porous silicon-based minerals as a substrate and a preparation method thereof. Background Art

[0002] As one of the important indicators of indoor environmental quality, the appropriate relative humidity range helps maintain the thermal comfort and health of the human body. In daily life, the comfortable relative humidity range for the human body is between 40% and 60%.

[0003] Too high or too low indoor relative humidity may have adverse effects on human health, indoor air quality, furniture, electrical appliances, etc. When the relative humidity is too high, it will inhibit the heat dissipation of the human body, causing moisture problems such as eczema, while promoting the growth of bacteria and mold, inducing respiratory diseases such as bronchitis and asthma, and easily causing damage to furniture and electrical appliances, moldy items, and electrical short circuit safety hazards. When the relative humidity is too low, it will cause dry skin, dry eyes, upper respiratory tract infection, and may also cause static electricity, cracking of wooden furniture, and yellowing of book paper, etc.

[0004] At present, humidity-control building materials have become the main development direction for controlling indoor humidity in buildings. They are mainly based on inorganic minerals such as zeolite, diatomaceous earth, and sepiolite, and the indoor relative humidity is adjusted through modification methods such as calcination and alkali washing.

[0005] Patent CN201810984402.8 discloses a humidity control purification material and a preparation method, application and products prepared by using the humidity control purification material, including diatomaceous earth, vermiculite powder, perlite powder, ethylene urea, plant fiber and negative ion powder in a specific ratio. Through the synergistic coordination between the specific components and ratios, the humidity control purification material provided by the present invention has a good humidity control effect, a large moisture capacity, and rapid humidity control. However, the moisture release capacity of the humidity control material and the environmental friendliness of the raw material selection still need to be further improved.

[0006] Patent CN 113150689 B discloses an anti-condensation coating, a preparation method and application thereof, wherein the coating comprises the following components by weight: 120-180 parts of water, 120-142.5 parts of humidity-controlling materials, and 7.5-30 parts of metal organic frameworks. Although this technology does have a certain humidity-controlling effect, the cost is high and the humidity-controlling effect needs to be further improved.

[0007] Existing humidity-control building materials still have problems such as limited humidity-control performance, complex processes, and high costs, which pose certain challenges to commercial production and user popularization. Summary of the invention

[0008] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a temperature and humidity regulating building material with porous silicon-based minerals as the substrate and a preparation method thereof, which has low cost and has both temperature and humidity regulating functions.

[0009] The purpose of the present invention can be achieved through the following technical scheme: a temperature and humidity regulating building material with porous silicon-based minerals as the substrate, comprising the following components in parts by weight: 3% to 22% potassium hydroxide, 2% to 16% silica gel, 0% to 7% phase change microcapsules, and the remainder silicon-based minerals.

[0010] Furthermore, the silicon-based minerals include one or more of perlite, coal gangue and metakaolin.

[0011] Furthermore, the particle size of the perlite is 20 to 200 meshes;

[0012] The particle size of the coal gangue is 20 to 50 meshes;

[0013] The particle size of the metakaolin is 7000-8000 meshes.

[0014] Furthermore, the silicon-based mineral is a mixture of perlite and metakaolin in a mass ratio of 26-42:30-36.

[0015] Furthermore, the silicon-based mineral is a mixture of coal gangue and metakaolin in a mass ratio of 65-88:6-18.

[0016] Further preferably, the usage of the phase change microcapsules is 1-7%.

[0017] The present invention also provides a method for preparing a temperature and humidity regulating building material using a porous silicon-based mineral as a substrate, comprising the following steps:

[0018] S1. Dissolve potassium hydroxide in water according to mass ratio, stir and mix evenly, and let it stand until the reactor returns to room temperature;

[0019] S2, adding silica gel and phase change microcapsules into the reactor according to the mass ratio, stirring and mixing evenly;

[0020] S3, adding silicon-based minerals into the reactor according to mass proportion, stirring and mixing evenly;

[0021] Use an electric stirrer to stir at a constant speed of 500 to 800 rpm for 20 to 30 minutes until the mixture is uniformly mixed to obtain a uniform mixture.

[0022] Furthermore, the standing time in step S1 is 10 to 15 minutes.

[0023] Furthermore, in step S2, the stirring speed is 500 to 800 rpm; and the stirring time is 5 to 10 min.

[0024] Furthermore, in step S3, the stirring speed is 500 to 800 rpm; and the stirring time is 20 to 30 min.

[0025] Compared with the prior art, the present invention has the following characteristics:

[0026] The temperature and humidity control coating provided by the present invention comprises raw materials including perlite / coal gangue, metakaolin, potassium hydroxide, silica gel, and phase change microcapsules. Among them, perlite, coal gangue and metakaolin are all porous silicate minerals. Perlite is a glassy rock formed by rapid cooling of lava from a volcanic eruption. After high-temperature roasting and expansion, a honeycomb structure is formed inside, and it has the characteristics of large specific surface area, rich pore structure, thermal insulation, sound absorption, etc. Coal gangue is a solid waste discharged during coal mining and washing, and has the characteristics of high silicon and aluminum content, large porosity, and hard structure. Improving the reuse of industrial solid waste such as coal gangue can also promote the friendly development of the ecological environment. The superior porosity of perlite and coal gangue is more conducive to the rapid and large-scale adsorption and release of moisture during the humidity control process, thereby reducing the fluctuation range of the relative humidity in the building interior with the external environment. Potassium hydroxide has the effect of alkaline excitation, which can change the chemical reaction process and crystal microstructure of the material. At the same time, part of the potassium hydroxide reacts with the silica gel powder to form potassium silicate, which helps to promote the effect of alkali excitation. As a porous geopolymer containing aluminosilicate, metakaolin undergoes a series of chemical reactions such as depolymerization, rearrangement and polycondensation under the action of potassium hydroxide and its silicate solution to form a gelling material with a three-dimensional network structure. The phase change temperature of the phase change microcapsules after mixing with different materials is 23-30°C, and the indoor temperature is maintained within a certain stable range by absorbing or releasing heat during the phase change process.

[0027] The present invention adjusts the internal microstructure of the material from micron-sized particles to a nanostructure by alkaline excitation, so that the overall porosity of the coating and the number of open pores below 10nm are increased. The temperature and humidity control coating not only has superior wet buffering performance than existing humidity control coatings on the market, but also provides a low-cost and simple process preparation method, which has both temperature and humidity control functions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The pore distribution diagram (a) and scanning electron microscope diagram (b) of the material obtained in Example 2;

[0029] Figure 2 The pore distribution diagram (a) and scanning electron microscope diagram (b) of the material obtained in Example 4;

[0030] Figure 3 The pore distribution diagram (a) and scanning electron microscope diagram (b) of the material obtained in Example 8;

[0031] Figure 4 The pore distribution diagram (a) and scanning electron microscope diagram (b) of the material obtained in Example 9;

[0032] Figure 5 It is a test bench for testing the effects of temperature and humidity regulating coating board products. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0034] The various raw materials used in the present invention are all commercially available raw materials in the art. For example, the phase change microcapsules used in the following embodiments are 25-degree phase change wax powder commercially available from Henan Shenyuzhixingkongtian Technology Co., Ltd.

[0035] The following is a detailed description with reference to embodiments.

[0036] Embodiment 1:

[0037] The present embodiment provides a humidity-controlling material, the components of which are as follows by mass: 26.3% perlite (particle size 20-35 mesh), 36.8% metakaolin (particle size 7000-8000 mesh), 21.1% potassium hydroxide, and 15.8% silica gel.

[0038] The preparation method is as follows:

[0039] (1) Dissolve potassium hydroxide in water according to the mass ratio, stir with a glass rod for 5 minutes until the mixture is uniform, and let it stand for 12 minutes until the reactor returns to room temperature.

[0040] (2) Add silica gel and phase change microcapsules into the reactor according to the mass ratio, and stir at 600 rpm for 8 minutes using an electric stirrer until the mixture is uniformly mixed.

[0041] (3) Adding metakaolin and perlite into the reactor in order according to the mass ratio, stirring at a constant speed of 600 rpm for 25 minutes with an electric stirrer until the mixture is uniformly mixed to obtain a uniform mixture.

[0042] Embodiment 2:

[0043] This embodiment provides a humidity control material, the components of which are as follows by mass: 41.7% perlite (particle size 20-35 mesh), 29.2% metakaolin (particle size 7000-8000 mesh), 16.6% potassium hydroxide, and 12.5% ​​silica gel. The preparation method is shown in Example 1.

[0044] Embodiment 3:

[0045] This embodiment provides a humidity control material, the components of which are as follows by mass: 58.8% perlite (particle size 20-35 mesh), 20.6% metakaolin (particle size 7000-8000 mesh), 11.7% potassium hydroxide, and 8.8% silica gel. The preparation method is shown in Example 1.

[0046] Embodiment 4:

[0047] This embodiment provides a temperature and humidity control material, the components of which are as follows by mass: 39.1% perlite (particle size 20-35 mesh), 27.3% metakaolin (particle size 7000-8000 mesh), 15.6% potassium hydroxide, 11.7% silica gel, and 6.3% phase change microcapsules. The preparation method is shown in Example 1.

[0048] Embodiment 5:

[0049] This embodiment provides a humidity control material, the components of which are as follows by mass: 39.1% perlite (particle size 35-50 mesh), 30.4% metakaolin (particle size 7000-8000 mesh), 17.4% potassium hydroxide, and 13.1% silica gel. The preparation method is shown in Example 1.

[0050] Embodiment 6:

[0051] This embodiment provides a humidity control material, the components of which are as follows by mass: 36.4% perlite (particle size 200 mesh), 31.8% metakaolin (particle size 7000-8000 mesh), 18.2% potassium hydroxide, and 13.6% silica gel. The preparation method is shown in Example 1.

[0052] Embodiment 7:

[0053] This embodiment provides a humidity control material, the components of which are as follows by mass: 65% coal gangue (particle size 20-40 mesh), 17.5% metakaolin (particle size 7000-8000), 10% potassium hydroxide, and 7.5% silica gel.

[0054] The preparation method is as follows:

[0055] (1) Dissolve potassium hydroxide in water according to the mass ratio, stir with a glass rod for 5 minutes until the mixture is uniform, and let it stand for 12 minutes until the reactor returns to room temperature.

[0056] (2) Add silica gel and phase change microcapsules into the reactor according to the mass ratio, and stir at 600 rpm for 8 minutes using an electric stirrer until the mixture is uniformly mixed.

[0057] (3) Adding metakaolin and coal gangue into the reactor in order according to the mass ratio, stirring at a constant speed of 600 rpm for 25 minutes with an electric stirrer until the mixture is uniformly mixed to obtain a uniform mixture.

[0058] Embodiment 8:

[0059] This embodiment provides a humidity control material, the components of which are as follows by mass: 87.5% coal gangue (particle size 20-40 mesh), 6.2% metakaolin (particle size 7000-8000 mesh), 3.6% potassium hydroxide, and 2.7% silica gel. The preparation method is shown in Example 7.

[0060] Embodiment 9:

[0061] This embodiment provides a temperature and humidity control material, the components of which are as follows by mass: 86.3% coal gangue (particle size 20-40 mesh), 6.1% metakaolin (particle size 7000-8000 mesh), 3.5% potassium hydroxide, 2.7% silica gel, and 1.4% phase change microcapsules. The preparation method is shown in Example 7.

[0062] Comparative Example 1:

[0063] This comparative example provides a material, the component of which is perlite (particle size 20-35 mesh).

[0064] Comparative Example 2:

[0065] This comparative example provides a material, the component of which is coal gangue (particle size 20-40 mesh).

[0066] Comparative Example 3:

[0067] This comparative example provides a humidity control material, the components of which are as follows by mass: 58.8% perlite (particle size 20-35 mesh), 23.5% potassium hydroxide, and 17.6% silica gel. The preparation method is as shown in Example 1.

[0068] Comparative Example 4:

[0069] This comparative example provides a humidity control material, the components of which are as follows by mass: 50% perlite (particle size 20-35 mesh), 35% metakaolin (particle size 7000-8000 mesh), and 15% silica gel. The preparation method is shown in Example 1.

[0070] Comparative Example 5:

[0071] This comparative example provides a humidity control material, the components of which are as follows by mass: 93.3% coal gangue (particle size 20-40 mesh), 3.8% potassium hydroxide, and 2.9% silica gel. The preparation method is shown in Example 7.

[0072] Comparative Example 6:

[0073] This comparative example provides a humidity control material, the components of which are as follows by mass: 90.7% coal gangue (particle size 20-40 mesh), 6.5% metakaolin (particle size 7000-8000 mesh), and 2.8% silica gel. The preparation method is shown in Example 7.

[0074] The formula table of each embodiment and comparative example is as follows Table 1:

[0075] Table 1 Formulations of Examples and Comparative Examples

[0076]

[0077] The performance tests of the materials obtained in each embodiment and comparative example are as follows:

[0078] (1) Wet buffer value:

[0079] Testing method: Use the wet buffer value and test method proposed by NordTest to evaluate the humidity control performance of materials under daily cycle changes, that is, after four cycles of moisture absorption and dehumidification at 75% relative humidity indoors for 8 hours and 32% relative humidity indoors for 16 hours, measure the moisture absorption or dehumidification per unit area of ​​the sample at unit relative humidity. The evaluation method for the humidity control performance level of the material is as follows: When the material thickness is more than 1cm, the wet buffer value is between 0 and 0.2 (g·m -2 %RH -1 ), the humidity adjustment effect can be ignored; the wet buffer value is between 0.2 and 0.5 (g·m -2 %RH -1 ), the humidity adjustment effect is limited; the wet buffer value is 0.5~1.0(g·m -2 %RH -1 ), the humidity control effect is moderate; the wet buffer value is 1.0~2.0 (g·m -2 %RH -1 ) when the humidity adjustment effect is good; the wet buffer value is 2 (g·m -2 %RH -1 ) or above, the humidity control effect is excellent.

[0080] Test results: The wet buffer value results of each embodiment and comparative example are shown in Table 2 below:

[0081] Table 2 Wet buffer values ​​of embodiments and comparative examples

[0082] <![CDATA[Wet buffer value (g·m -2 ·%RH -1 )]]> Example 1 4.5 Example 2 3.5 Example 3 2.9 Example 4 4.2 Example 5 3.5 Example 6 2.9 Example 7 2.1 Example 8 4.2 Example 9 3.4 Comparative Example 1 0.18 Comparative Example 2 0.23 Comparative Example 3 1.2 Comparative Example 4 1.4 Comparative Example 5 1.1 Comparative Example 6 1.2 .

[0083] It can be seen from Table 2 above that the wet buffer value of each embodiment is 2.1 g·m -2 %RH -1 The above, especially Example 1 reached 4.5 g·m -2 %RH -1 As shown above, the wet buffer value of pure perlite or coal gangue is very low, and the excess potassium hydroxide in Comparative Example 3 will also reduce the wet buffer value. The wet buffer values ​​of Comparative Examples 4 and 6 without potassium hydroxide are relatively low.

[0084] In existing reports, Chinese patent CN 113150689 B discloses a humidity-regulating and anti-condensation coating. The metal organic framework MIL-100 (Fe) component involved is expensive and has a humidity-regulating performance of only 2.1 g·m -2 %RH -1 The humidity control material provided by the present invention greatly saves the cost of raw materials, and the humidity control performance can be improved to more than 1.5 to 2 times.

[0085] (2) Pore size distribution and morphology detection

[0086] Figure 1 The pore distribution diagram (a) and scanning electron microscope diagram (b) of the material obtained in Example 2 show that the material has honeycomb pores; the number of mesopores around 3 nm accounts for the largest proportion, accounting for 31% of the total number of pores; the number of mesopores between 2 and 10 nm accounts for 97%; the macropores larger than 50 nm account for the largest total pore volume, with a volume of 8×10 -3 cm 3 / g.

[0087] Figure 2 The pore distribution diagram (a) and scanning electron microscope diagram (b) of the material obtained in Example 4 show that the material has a large number of honeycomb pores; the number of mesopores around 3 nm accounts for the largest proportion, accounting for 22% of the total number of pores; the number of mesopores between 2 and 10 nm accounts for 95%; the macropores larger than 50 nm account for the largest total pore volume, with a volume of 7×10 -3 cm 3 / g.

[0088] Figure 3 The pore distribution diagram (a) and scanning electron microscope diagram (b) of the material obtained in Example 8 show that the material has honeycomb pores and crack-like depressions on the surface; the number of mesopores around 1 nm accounts for the largest proportion, accounting for 42% of the total number of pores; the number of micropores less than 2 nm accounts for 76% of the total number of pores, and the number of mesopores between 2 and 10 nm accounts for 23%; the macropores greater than 50 nm account for the largest total pore volume, with a volume of 1×10 -3 cm 3 / g.

[0089] Figure 4 The pore distribution diagram (a) and scanning electron microscope diagram (b) of the material obtained in Example 9 show that the material has a large number of honeycomb pores and fibrous structures; the number of mesopores around 1 nm accounts for the largest proportion, accounting for 55% of the total number of pores; the number of micropores less than 2 nm accounts for 83% of the total number of pores, and the number of mesopores between 2 and 10 nm accounts for 16%; the macropores greater than 50 nm account for the largest total pore volume, with a volume of 4×10 -3 cm3 / g.

[0090] It can be seen that the material of the present application has good porous properties, and the microscopic pores are mainly concentrated in micropores and mesopores below 10 nm, which helps to improve the moisture absorption and release capacity of the material.

[0091] (3) Application detection

[0092] A test bench for testing the effect of the humidity-controlling coating plate product of the present invention is constructed.

[0093] A sealed plastic box (40 cm × 30 cm × 15 cm) was used to simulate a small enclosed space, and the south and east sides were shielded with insulation boards to prevent solar radiation from interfering with the experiment. Figure 5 As shown. A 10cm×10cm×2cm humidity-controlling coating plate of Example 2 of the present invention is placed in one sealed box; a 10cm×10cm×2cm humidity-controlling coating plate of Example 5 of the present invention is placed in another sealed box; and the other sealed box is an empty box without a humidity-controlling plate.

[0094] By monitoring the relative humidity changes in the outdoor natural environment and in two sealed boxes throughout June 2024, the effect of using the temperature and humidity regulating coating board product of the present invention is evaluated. The monitoring results are shown in Table 3 below:

[0095] Table 3 Effect of the temperature and humidity regulating coating plate product of the present invention

[0096]

[0097]

[0098] It can be seen from Table 3 above that the temperature and humidity regulating coating board product of the present invention has a very good automatic moisture absorption and release regulation effect, and the monthly cycle change and daily cycle maximum change of the relative humidity in the sealed box are significantly smaller than the internal and outdoor environments of the sealed box without temperature and humidity regulating boards.

[0099] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A temperature and humidity control building material based on porous silicon-based minerals, characterized in that: The invention comprises the following components in parts by weight: 3% to 22% potassium hydroxide, 2% to 16% silica gel, 0% to 7% phase change microcapsules and the remainder silicon-based minerals.

2. The temperature and humidity regulating building material based on porous silicon-based minerals according to claim 1, characterized in that: The silicon-based minerals include one or more of perlite, coal gangue and metakaolin.

3. The temperature and humidity regulating building material based on porous silicon-based minerals according to claim 2, characterized in that: The particle size of the perlite is 20 to 200 meshes; The particle size of the coal gangue is 20 to 50 meshes; The particle size of the metakaolin is 7000-8000 meshes.

4. The temperature and humidity regulating building material based on porous silicon-based minerals according to claim 2, characterized in that: The silicon-based mineral is a mixture of perlite and metakaolin in a mass ratio of 26-42:30-36.

5. The temperature and humidity regulating building material based on porous silicon-based minerals according to claim 2, characterized in that: The silicon-based mineral is a mixture of coal gangue and metakaolin in a mass ratio of 65-88:6-18.

6. The temperature and humidity regulating building material based on porous silicon-based minerals and the preparation method thereof according to claim 1, characterized in that: The dosage of the phase change microcapsules is 1-7%.

7. A method for preparing a temperature and humidity regulating building material based on porous silicon-based minerals as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Dissolve potassium hydroxide in water according to mass ratio, stir and mix evenly, and let it stand until the reactor returns to room temperature; S2, adding silica gel and phase change microcapsules into the reactor according to the mass ratio, stirring and mixing evenly; S3, adding silicon-based minerals into the reactor according to mass proportion, stirring and mixing evenly; Use an electric stirrer to stir at a constant speed of 500 to 800 rpm for 20 to 30 minutes until the mixture is uniformly mixed to obtain a uniform mixture.

8. The method for preparing a temperature and humidity regulating building material based on porous silicon-based minerals according to claim 7, characterized in that: The standing time in step S1 is 10 to 15 minutes.

9. The method for preparing a temperature and humidity regulating building material based on porous silicon-based minerals according to claim 7, characterized in that: In step S2, the stirring speed is 500 to 800 rpm; and the stirring time is 5 to 10 min.

10. The method for preparing a temperature and humidity regulating building material based on porous silicon-based minerals according to claim 7, characterized in that: In step S3, the stirring speed is 500 to 800 rpm and the stirring time is 20 to 30 min.

Citation Information

Patent Citations

  • Humidifying and purifying material, preparation method and application thereof, as well as product prepared by applying humidifying and purifying material

    CN108947470A

  • An anti-condensation coating, its preparation method and application

    CN113150689B

  • Temperature adjusting humidity adjusting coating and preparation method thereof

    CN103159437A

  • Composite geopolymer lightweight moisture-regulating material and preparation method thereof

    CN109250964A

  • Anti-condensation coating, coating layer, product, and preparation method and application of the coating

    CN110835484A